Sistem Pendidikan Arab Saudi: Analisis Historis, Filosofis, Sosiologis, Yuridis, dan Implementasi Kebijakan Pendidikan Kontemporer: The Education System of Saudi Arabia: A Historical, Philosophical, Sociological, and Juridical Analysis, and the Implementation of Contemporary Educational Policies - Siti Fathonah; Agus Faisal Asyha (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This article examines Saudi Arabia's education system by focusing on the relationship between Islamic identity, institutional structure, and contemporary education reform under Vision 2030. The study is important because previous works often describe Saudi education in a general manner, while less attention is given to the tension between Islamic values, curriculum modernization, access equity, and global competitiveness. This study applies a library research method with narrative synthesis of official documents, international reports, and scholarly publications from 2015 to 2026. The findings show that Saudi education has moved from traditional mosque and kuttab-based learning to a centralized, free, and structured national system. Vision 2030 has strengthened learning quality, digital transformation, vocational education, research capacity, and alignment between education and labor-market needs. Nevertheless, the system still faces challenges in balancing religious authority, twenty-first century competencies, regional equity, and graduate quality. The article argues that the Saudi experience contributes to comparative Islamic education studies, especially in explaining how a Muslim state reforms education while maintaining religious foundations.